2006
DOI: 10.1021/cm061797h
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Peroxo-titanate Materials Tailored for Optimal Strontium and Actinide Sorption

Abstract: Achieving global optimization of inorganic sorbent efficacy, as well as tailoring sorbent specificity for target sorbates would facilitate increased wide-spread use of these materials in applications such as producing potable water or nuclear waste treatment. Sodium titanates have long been known as sorbents for radionuclides;90 Sr and transuranic elements in particular. We have developed a related class of materials, which we refer to as peroxo-titanates: these are sodium titanates or hydrous titanates proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 41 publications
1
71
0
Order By: Relevance
“…7 After adding the sorbents, the bottles were placed in the waterbath shaker, maintained at an average temperature of 23.59 ± 0.67 °C, and were continually shaken. Samples were removed at times of 6,12,24,48, and 72 hours, and then weekly for a total of 6 weeks.…”
Section: Orbital Shaker Testsmentioning
confidence: 99%
“…7 After adding the sorbents, the bottles were placed in the waterbath shaker, maintained at an average temperature of 23.59 ± 0.67 °C, and were continually shaken. Samples were removed at times of 6,12,24,48, and 72 hours, and then weekly for a total of 6 weeks.…”
Section: Orbital Shaker Testsmentioning
confidence: 99%
“…During the development of the synthesis for modified MST (mMST), which involves the treatment of MST with H 2 O 2 to form a peroxo-titanate, some dissolution of the MST was observed, and it was reported that this dissolution was likely due to excess peroxide present in the synthesis. 12 The soluble Ti concentration in this experiment was much greater than observed in other CCPO experiments performed using the full simulant make-up, including the TPB. In experiments performed with TPB present, the maximum soluble Ti concentration measured was 62 ppm, which represents dissolution of ~9.4% of the MST available.…”
Section: Figure 3-4 U Concentration In Solution During Simulated Tanmentioning
confidence: 51%
“…The first simulant (A -normal prep) was prepared following the general procedure described in the previous paragraph, adding the stable Sr in the form of Sr(NO 3 ) 2 and the 85 Sr tracer to the simulant separately, but while the solution was still acidic. In the second simulant (B -combined addition), the Sr(NO 3 ) 2 was first dissolved in a small volume of water. The 85 Sr tracer was then added to this solution, and the solution was evaporated to dryness.…”
Section: Simulant Preparationmentioning
confidence: 99%
“…The mMST used in these experiments, batch LS-10, was prepared in the lab by treating a sample of the Optima 00-QAB-417 material with hydrogen peroxide following a previously published procedure. 2 The bottles were then placed in the shaker oven and agitated for 24 hours. After 24 hours, samples were removed and filtered through a 0.1 μm polyvinylidene fluoride (PVDF) syringe filter to remove the solids.…”
Section: Simulant Preparationmentioning
confidence: 99%